Assessment of Registered Nurses' Competencies in Chemotherapy Care Competencies and their Predictors in a Thai Tertiary Hospital - Saelor, Bangorn; Thasaneesuwan, Samonnan (Fakultas Ilmu-ilmu Kesehatan, 2025)
This descriptive correlational study examined the competencies of professional nurses in caring for adult and older adult cancer patients undergoing chemotherapy at a hospital in southern Thailand. The sample consisted of 100 professional nurses, with data collected between April and May 2024. The instruments included a demographic questionnaire and a competency questionnaire, with strong reliability (Cronbach’s alpha = .97). Data were analyzed using descriptive statistics, Spearman’s correlation, and the Mann-Whitney U test. The results showed that nurses’ overall competencies in caring for adult and older adult cancer patients undergoing chemotherapy were at a high level (Mean = 2.73, SD = 0.52). The three highest-rated competencies were ethics and patient rights (Mean = 3.24, SD = 0.53), patient preparation before, during, and after chemotherapy (Mean = 2.77, SD = 0.62), and communication, teaching, and providing information (Mean = 2.71, SD = 0.66). Furthermore, both experience in chemotherapy care and participation in cancer-related training were significantly associated with higher competency levels (r = 0.37, p < .001; Z = 4.209, p < .001). These findings highlight key areas for professional development and may guide future efforts to strengthen oncology nursing competencies.